2005
DOI: 10.1016/j.carbon.2005.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of herringbone and stacked-cup carbon nanofibers

Abstract: Due to their small size and their extraordinary physicochemical properties [1][2][3], much attention has been paid to the interesting sp 2 -based fibrous carbons, including carbon nanotubes. It is generally accepted that carbon nanotubes consist of single or multiple graphene sheets rolled into concentric cylinders: thus giving rise to single wall carbon nanotubes (SWNTs) or multi-walled carbon nanotubes (MWNTs) [4,5]. Recently, we described a new type of carbon nanofiber, "stacked-cup carbon nanofiber", which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…While the type of catalyst (Fe vs Ni) does not seem important for producing this type of CNFs, the presence of sulfur seems to be indispensable to produce of this unique structure. Kim et al [24] suggested that the catalyst particle must be molten, and according to Tibbetts et al [38], the presence of sulfur causes the catalyst particles to melt due to an eutectic in the Fe-S system at 1271 K and at a 42 at.% of S. This molten state increases the catalytic activity, which allows to reduce the residence time considerably and, in turn, mitigates the non-catalytic CVD coating (or soot) formation. The quantity of sulfur in the feedstock cannot be random and must be on a similar atomic ratio to iron.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While the type of catalyst (Fe vs Ni) does not seem important for producing this type of CNFs, the presence of sulfur seems to be indispensable to produce of this unique structure. Kim et al [24] suggested that the catalyst particle must be molten, and according to Tibbetts et al [38], the presence of sulfur causes the catalyst particles to melt due to an eutectic in the Fe-S system at 1271 K and at a 42 at.% of S. This molten state increases the catalytic activity, which allows to reduce the residence time considerably and, in turn, mitigates the non-catalytic CVD coating (or soot) formation. The quantity of sulfur in the feedstock cannot be random and must be on a similar atomic ratio to iron.…”
Section: Discussionmentioning
confidence: 99%
“…1h. Although these nanofibers were previously described as either a Pd catalyzed product [22] with small diameters around 20 nm or a Fe derived nanofiber with a huge hollow space [23], Kim et al [24] recently stated that the stackedcup nanofibers have a circular cross-section and are different to fishbone nanofibers even though the TEM pictures look like the same. These authors also stated that stacked-cup carbon nanofibers, with a huge hollow space, are catalyzed with a molten particle.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cup-stacked carbon nanotubes are excellent as supports for Pt-Ru catalysts [77] and have been synthesized with a diameter of 80-120 nm and a hollow channel of 60-100 nm along the nanotube axis [78]. This configuration is shown in Figure 4 [79]. For carbon peapods, however, stability is probably compromised since it was shown that the axial stability is less than that of a carbon nanotube under identical conditions [80].…”
Section: Categories Of Carbon Nanotubesmentioning
confidence: 99%